Simvastatin in primary and secondary prevention of cerebrovascular insufficiency - E. A. Melnik; G. A. Vlasova; A. Yu. Savchenko (Кардиоваскулярная терапия и профилактика)
Aim. To study simvastatin effects on lipid profile and cognitive function in patients with various cerebral ischemia variants. Material and methods. In total, 210 patients with cerebrovascular disease and dyslipidemia (DLP) were divided into three groups. Group A (n=108; primary carotid ischemic stroke) and Group B (n=68; Stage I-II dyscirculatory encephalopathy, DCE), took simvastatin for 24 months. Group C (n=34; Stage I-II DCE) did not take simvastatin. Lipid profile (LP) assessment, extracranial Doppler ultrasound, rheoencephalography, neurovisualization, neuro-psychological and statistical analyses were performed. LP was measured at baseline, 6, 12, 24 months later; cerebral hemodynamics and cognitive status parameters – at baseline and 24 months later. Results. Two-year follow-up and simvastatin treatment (10-20 mg/d) of cerebrovascular insufficiency patients demonstrated positive results. There was a statistically significant decrease in total cholesterol (CH), low-density lipoprotein CH, and triglycerides levels, as well as in atherogenic index, combined with increase in high-density lipoprotein CH concentration. Simvastatin demonstrated pleiotropic effects. Speech function improvement was also observed (р<0,05). Conclusion. Simvastatin had stable lipid-lowering and cognitive status-improving effects. The medication was highly effective and well-tolerated.